2018
DOI: 10.1002/asia.201800174
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Bonding in Bowl‐Like B36 Cluster Revisited: Concentric (6π+18π) Double Aromaticity and Reason for the Preference of a Hexagonal Hole in a Central Location

Abstract: The bowl-shaped C B cluster with a central hexagon hole is considered an ideal molecular model for low-dimensional boron-based nanosystems. Owing to the electron deficiency of boron, chemical bonding in the B cluster is intriguing, complicated, and has remained elusive despite a couple of papers in the literature. Herein, a bonding analysis is given through canonical molecular orbitals (CMOs) and adaptive natural density partitioning (AdNDP), further aided by natural bond orbital (NBO) analysis and orbital com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Coronene C 12 H 24 is one of the most remarkable and intriguing molecules in organic chemistry. Although it was first synthesized almost a century ago it is still in focus , because of its unusual structure which remains a conundrum. As a big planar polycyclic molecule formally containing 24 π-electrons, coronene does not correspond to aromatic molecules which follow the 4 n + 2 Huckel’s rule so its well-known experimental stability could not be theoretically substantiated by simple counting of conjugated system π-electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Coronene C 12 H 24 is one of the most remarkable and intriguing molecules in organic chemistry. Although it was first synthesized almost a century ago it is still in focus , because of its unusual structure which remains a conundrum. As a big planar polycyclic molecule formally containing 24 π-electrons, coronene does not correspond to aromatic molecules which follow the 4 n + 2 Huckel’s rule so its well-known experimental stability could not be theoretically substantiated by simple counting of conjugated system π-electrons.…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades combined experimental and theoretical studies have been systematically undertaken to characterize the structure and bonding properties of size-selected boron clusters. [1][2][3][4] Bare boron clusters can adopt a diverse variety of geometric structures, such as planar, 1 quasi-planar, 1,4 bowl, 5,6 cage, 7 tubular, 8,9 multiple ring 10 and fullerene-like structures. 11 Isolated bare boron clusters exhibit different geometrical shapes from the clusters found as building blocks in the bulk phase of elemental boron.…”
Section: Introductionmentioning
confidence: 99%
“…As the nearest neighbor of carbon in the periodic table, boron is a typical electron-deficient element, which leads to unique structures and chemical bonding for boron-based nanoclusters and low-dimensional nanomaterials. Over the past 30 years, systematic experimental and computational studies have shown that boron clusters exhibit planar or quasi-planar (2D) structures in a wide range of sizes. For example, anionic 2D boron clusters were observed and characterized up to 40 atoms, B 40 – , via photoelectron spectroscopy (PES) in the gas phase, which coexists with cage-like borospherene .…”
Section: Introductionmentioning
confidence: 99%